Syllepse et antanaclase : procédés rhétoriques dans le slogan publicitaire - Sivia Boncescu (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2018)
This study concentratres upon the lexical strategies that include figures and rhetorical devices like metaphor or metonymy and their functioning in advertising messages. The identified figures of rhetoric are used to support and increase advertising effectiveness and are responsible for creativity in advertising.